البطل الإشكالي في المجموعة القصصية "أرض البرتقال الحزين" لغسان كنفاني - عبد الغني فطحيزة عمار; يوسف مدب; خليفة بوعزة (university of el oued, 2025)
من القضايا النقدية المطروقة في القصة الحديثة قضية البطل الإشكالي والتي دار حولها نقاش مستفيض بين النقاد، وتبين أن البطل الإشكالي كشخصية رئيسة ومسؤولة عن دينامية الحدث لها تمظهرات كثيرة مرتبطة بتصورات الكاتب وخلفياته الأيديولوجية، كما هو الشأن في المجموعة القصصية "أرض البرتقال الحزين" للكاتب الفلسطيني غسان كنفاني. للإجابة عن هذه الإشكالية وضعنا خطة نحسبها تفي بالغرض تشتمل على مدخل نظري حول السياق الثقافي لصاحب المجموعة الذي عرّفنا بحياته وأعماله، ثم فصلين اثنين أحدهما نظري عرضنا فيه المفاهيم الأساسية للبطل والبطل الإشكالي وأنواع البطل وتمظهرات البطل الإشكالي بين الدافع الأيديولوجي والمنظور النصي، ثم تناولنا البطل الإشكالي وعلاقته بالقضية الفلسطينية. أما في الفصل التطبيقي تم التطرق إلى المجموعة القصصية أرض البرتقال الحزين بحيث حللنا مجموعة منتقاة من الأبطال الإشكاليين كالبطل الفلسفي والأخلاقي والتاريخي والخرافي والواقعي. One of the critical issues addressed in modern fiction is the problematic hero, which has been the subject of extensive discussion among critics. It has become clear that the problematic hero, as a central figure responsible for the dynamics of the event, has many manifestations linked to the writer's perceptions and ideological background, as is the case in the short story collection "Land of Sad Oranges" by Palestinian author GhassanKanafani. To answer this problem, we developed a plan that we believe is adequate. It includes a theoretical introduction to the cultural context of the author of the collection, introducing his life and works. Then, we have two chapters, one of which is theoretical, in which we present the basic concepts of the hero and the problematic hero, the types of heroes, and the manifestations of the problematic hero between ideological motivation and textual perspective. We then discussed the problematic hero and his relationship to the Palestinian cause. In the applied chapter, we addressed the short story collection "Land of Sad Oranges," analyzing a selected group of problematic heroes, including philosophical, moral, historical, mythical, and realistic heroes.
مذكرة ماستر .أدب حديث ومعاصر 2025
Keywords: جماليات المديح النبوي -الشعر السردي -الشعر الخيالي; Aesthetics of Prophetic Praise - Narrative Poetry - Imaginative Poetry